New Cognitive practices in a Master’s Thesis Proposal Writing Seminar - Carlino, Paula (2023)
This chapter explores Bazerman´s notion that genres shape the ways of thinking of those who participate in them as genres channel their cognitive activity according to the social practices that they help organize. The chapter analyzes videotaped classroom interactions in a master´s thesis proposal writing seminar. It identifies five types of specialized cognitive practices that master´s students begin to engage in, and characterizes the interactive pedagogy, centered on joint reviews, carried out in the context of the covid-19 pandemic. These collective reviews are both a device for genre learning and a methodological resource that allows the researcher to gain access to clues about the intellectual processes of those who write and talk about texts.